Teacher emotion research : introducing a conceptual model to guide future research - Fried, Leanne; Mansfield, Caroline; Dobozy, Eva (Issues in educational research, 2015)
This article reports on the development of a conceptual model of teacher emotion through a review of teacher emotion research published between 2003 and 2013. By examining 82 publications regarding teacher emotion, the main aim of the review was to identify how teacher emotion was conceptualised in the literature and develop a conceptual model to illustrate the findings. Interestingly, few articles explicitly defined 'emotion' or 'teacher emotion' but described the functions of emotion (such as providing information) and influences on emotion (such as personal characteristics), so these were also used to build the conceptual model. The literature also highlighted the complexities of emotion, with implications for how teacher emotion should be studied. The model proposed aims to clarify how emotion research has been conceptualised within education research contexts. [Author abstract]